Main problems of auditing in Ukraine - Postnikova, Vera (My University, 2014)
Among the factors of successful economic development of the modern state a big attention is paid to introduction of effective forms of independent financial control. Auditing belongs to this type of activity. An audit is an independent examination of financial statements of business enterprises by authorized persons (auditors) to confirm its authenticity to tax authorities and owners. The audit is intended to provide assistance to representatives of insurance companies, stock exchanges, joint stock companies, joint ventures, commercial banks, various foreign companies. The object of audit - to promote efficiency, rational use of materials, labor and financial resources in business to maximize profits.
Keywords: economic development; financial report; audit; економічний розвиток; фінансовий звіт; аудит